The fragile state: essays on luminosity, normativity and metaphilosophy - Srinivasan, A (2013)
This dissertation is a set of three essays connected by the common theme of our epistemic fragility: the way in which our knowledge – of our own minds, of whether we are in violation of the epistemic and ethical norms, and of the philosophical truths themselves – is hostage to forces outside our control. The first essay, “Are We Luminous?”, is a recasting and defence of Timothy Williamson’s argument that there are no non-trivial conditions such that we are in a position to know we are in them whenever we are in them. Crucial to seeing why Williamson’s anti-luminosity argument succeeds, pace various critics, is recognising that the issue is largely an empirical one. It is in part because of the kind of creatures we are – specifically, creatures with coarse-grained doxastic dispositions – that nothing of interest, for us, is luminous. In the second essay, “What’s in a Norm?”, I argue that such an Anti-Cartesian view in turn demands that epistemologists and ethicists accept the ubiquity of normative luck, the phenomenon whereby agents fail to do what they ought because of non-culpable ignorance. Those who find such a view intolerable – many epistemic internalists and ethical subjectivists – have the option of cleaving to the Cartesian orthodoxy by endorsing an anti-realist metanormativity. The third essay, “The Archimedean Urge”, is a critical discussion of genealogical scepticism about philosophical judgment, including evolutionary debunking arguments and experimentally-motivated attacks. Although such genealogical scepticism often purports to stand outside philosophy – in the neutral terrains of science or common sense – it tacitly relies on various first-order epistemic judgments. The upshot is two-fold. First, genealogical scepticism risks self-defeat, impugning commitment to its own premises. Second, philosophers have at their disposal epistemological resources to fend off genealogical scepticism: namely, an epistemology that takes seriously the role that luck plays in the acquisition of philosophical knowledge.